SiC edge ring and preparation method and application thereof
Through densification treatment and SiC coating deposition technology, SiC Edge-Ring parts with sandwich structure are formed, solving the problems of high manufacturing cost, low purity, high impurity content and light transmittance of SiC Edge-Ring parts in the prior art, resulting in poor temperature uniformity, and low cost, high purity, low impurity, opaque light, and temperature uniformity.
Patent Information
- Application Number
- CN202510110284.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-23
- Publication Date
- 2025-02-28
AI Technical Summary
The SiC Edge-Ring components prepared in the prior art are expensive to manufacture, have low purity, high impurity content and poor light transmittance, resulting in poor temperature uniformity.
The SiC Edge-Ring component with a sandwich structure is formed by densifying the SiC ceramic core layer and depositing a SiC coating with accurate and controllable thickness on its surface and lower surface respectively.
SiC Edge-Ring components with low cost, high purity, low impurity, opaque light and temperature uniformity are achieved, meeting the needs of rapid wafer heat treatment process.
Smart Images

Figure CN119530756A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of semiconductor devices, and in particular to a SiC edge ring and a preparation method and application thereof. Background Art
[0002] With the continuous development of semiconductor technology, in order to reduce the cost of chips, the size of Si wafers has developed to 12 inches, and the number of transistors contained on a single wafer has increased significantly. In order to eliminate defects and stress in the wafer and improve product performance, it is necessary to perform rapid heat treatment on the wafer after ion implantation, thin film deposition and other processes. The rapid annealing furnace is a key equipment for rapid thermal annealing of wafers, and plays an increasingly important role in the semiconductor manufacturing process. Among them, the SiC edge ring (Edge-Ring) component, as one of the important ceramic components of the rapid annealing furnace, is in direct contact with the Si wafer, and plays the function of supporting the wafer and uniforming the wafer temperature. During use, it must withstand long-term and severe rapid heating / cooling thermal shock cycle conditions. The mechanical and thermal conductivity of the SiC Edge-Ring component and the uniformity of the material and performance directly affect the service life of the component, as well as the heat treatment effect of the Si wafer and the working efficiency and stability of the rapid annealing furnace.
[0003] In the prior art, the preparation methods of SiC Edge-Ring components include reaction sintering, chemical vapor deposition and hot pressing. The SiC Edge-Ring components obtained by reaction sintering are low in cost, but have low purity and contain a large amount of impurity elements, too much Si and unreacted C remain in the components, and the material uniformity is poor; the SiC Edge-Ring components prepared by chemical vapor deposition (CVD) are very high in purity, but have light transmittance in the range of 200 ~ 1500 nm, resulting in poor temperature uniformity of the components during use; the SiC Edge-Ring components prepared by hot pressing have both high purity and very low light transmittance, but the manufacturing cost is high. In summary, from the perspectives of both localization and performance, it is urgent to develop an innovative SiC Edge-Ring component for rapid annealing furnace and its preparation method. Summary of the invention
[0004] In view of the deficiencies in the above-mentioned background technology, the present invention mainly solves the technical problems of high manufacturing cost, low purity, high impurity content, and poor temperature uniformity caused by light transmission of SiCEdge-Ring components prepared in the prior art. The present invention provides a SiC edge ring and a preparation method and application thereof. The method helps to reduce the porosity of the SiC ceramic core layer through densification treatment, and deposits a SiC coating with a precisely controllable thickness on the surface of the SiC ceramic core layer, thereby avoiding the problem of cracking and shedding of the surface coating caused by thermal mismatch between the core layer and the surface coating.
[0005] The first object of the present invention is to provide a method for preparing a SiC edge ring, comprising the following steps: Preparing a ring-shaped SiC ceramic core layer; Densification treatment of SiC ceramic core layer; SiC coatings are deposited on the upper surface and the lower surface of the SiC ceramic core layer after densification treatment to obtain SiC edge rings.
[0006] Preferably, the thickness of the annular SiC ceramic core layer is 0.1-0.3 mm.
[0007] Preferably, the annular SiC ceramic core layer is prepared according to the following steps: Prepare SiC ceramic slurry with a volume fraction of ≥70 vol%; The SiC ceramic slurry is molded into a ring-shaped SiC ceramic body by a slip injection molding method; The SiC ceramic body is sequentially debinded and sintered to obtain a ring-shaped SiC ceramic core layer; The temperature during debinding is 600-1000°C and the debinding time is 1-3 hours. The sintering temperature is 1700-2100°C and the sintering time is 0.5-3h.
[0008] Preferably, when the SiC ceramic core layer is subjected to densification treatment, one or a combination of chemical vapor infiltration method, polymer impregnation cracking method, and reactive melt infiltration method is used to perform densification treatment on the SiC ceramic core layer once or multiple times.
[0009] Preferably, the volume density of the SiC ceramic core layer after densification treatment is 2.5 to 3.2 g / cm 3 .
[0010] Preferably, the thickness of the SiC coating is 0.05 to 0.20 mm; the SiC coating is dense and has no pore defects, and the grain size in the SiC coating is 0.5 to 20 μm.
[0011] Preferably, SiC coatings are deposited on the upper surface and the lower surface of the SiC ceramic core layer after densification treatment, respectively, comprising: The densified SiC ceramic core layer was placed in a chemical vapor deposition furnace, with MTS, H2 and Ar as the reaction gas, carrier gas and diluent gas respectively, and deposited at 1250-1400°C for 10-30h. Among them, the volume ratio of MTS, H2 and Ar is 1: (5-10): (1-3); The MTS flow rate is 0.5~1.5L / min; the H2 flow rate is 2.5~7.5L / min; and the Ar flow rate is 1.0~4.5L / min.
[0012] Preferably, after depositing SiC coatings on the upper and lower surfaces of the densified SiC ceramic core layer, the method further comprises: fine-machining the SiC ceramic core layer with the SiC coatings by a precision rotary table grinder, with a feed rate of 0.5-6 μm / min and a surface roughness Ra of less than 0.2 μm after machining.
[0013] A second object of the present invention is to provide a SiC edge ring.
[0014] The third object of the present invention is to provide an application of a SiC edge ring in wafer annealing.
[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a SiC edge ring and a preparation method and application thereof. The SiC Edge-Ring component for a rapid annealing furnace provided by the present invention has a sandwich structure feature, that is, it is composed of an ultra-thin SiC ceramic located in the core and a CVD SiC coating on the surface. The SiC Edge-Ring component preparation method provided by the present invention has the advantages of low requirements for sintering equipment, small net size processing amount, high surface purity, excellent thermal conductivity, low preparation cost, and good opaque temperature uniformity, and can meet the use requirements of wafer rapid thermal processing process.
[0016] The thickness of the SiC ceramic core layer prepared by the present invention is less than the thickness of the final component (0.4 mm), providing a template for the deposition of the surface CVD SiC coating, and the template can be used as a part of the SiC Edge-Ring component, reducing the deposition time of the CVD SiC coating, which is conducive to significantly reducing the manufacturing cost.
[0017] The present invention adopts one or a combination of chemical vapor infiltration technology, polymer impregnation and cracking technology, and reactive melt infiltration technology to perform one or more densification treatments on the ultra-thin SiC ceramic core layer, which helps to reduce the porosity of the ultra-thin SiC ceramic core layer, greatly increase the reflection path of incident light in the ultra-thin SiC ceramic core layer, form efficient absorption of incident light, significantly reduce light transmittance, and improve the temperature uniformity of components under operating conditions.
[0018] The present invention uses chemical vapor deposition to deposit a SiC coating with a precisely controllable thickness on the surface of an ultra-thin SiC ceramic core layer, and the thickness of the SiC coating is controlled in the range of 0.05 to 0.20 mm, which has the following advantages: the SiC coating and the SiC ceramic core layer prepared by the chemical deposition method are both SiC in terms of material, and the difference in thermal expansion coefficient is very small and negligible, which avoids the problem of cracking and shedding of the surface coating caused by thermal mismatch between the core layer and the surface coating. The precise and controllable coating deposition thickness helps to deposit to the tolerance size range required by the SiC Edge-Ring component at one time, greatly reducing the finishing time and cost, and greatly increasing the production efficiency and processing yield of the SiC Edge-Ring component. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 This is a product photo of the SiC Edge-Ring component prepared in Example 2.
[0020] Figure 2 This is a cross-sectional SEM image of the SiC Edge-Ring component product prepared in Example 2.
[0021] Figure 3 This is a product photo of the SiC Edge-Ring component prepared in Example 4.
[0022] Figure 4 This is a cross-sectional SEM image of the SiC Edge-Ring component product prepared in Example 4.
[0023] Figure 5 This is the surface XRD diagram of the SiC Edge-Ring component product prepared in Example 1.
[0024] Figure 6 This is the light transmittance test result of the SiC Edge-Ring component product prepared in Example 6.
[0025] Figure 7 This is the bending strength test result of the SiC Edge-Ring component product prepared in Example 4. DETAILED DESCRIPTION
[0026] In order to enable those skilled in the art to better understand and implement the technical solution of the present invention, the present invention is further described below in conjunction with specific embodiments and drawings, but the embodiments are not intended to limit the present invention.
[0027] The purpose of the present invention is to provide a SiC edge ring and a preparation method and application thereof, so as to solve the technical problems of high manufacturing cost, low purity, high impurity content and poor temperature uniformity caused by light transmission of SiC edge ring components prepared in the prior art.
[0028] In order to achieve the above object, the present invention provides a method for preparing a SiC edge ring in a first aspect, comprising the following steps: Preparing a ring-shaped SiC ceramic core layer; Densification treatment of SiC ceramic core layer; SiC coatings are deposited on the upper surface and the lower surface of the SiC ceramic core layer after densification treatment to obtain SiC edge rings.
[0029] The SiC Edge-Ring component for the rapid annealing furnace of semiconductor manufacturing equipment provided by the present invention has a sandwich structure feature, that is, it is composed of an ultra-thin SiC ceramic located in the core and a CVD SiC coating on the surface. The SiCEdge-Ring component preparation method provided by the present invention has the advantages of low requirements for sintering equipment, small net size processing, high surface purity, excellent thermal conductivity, low preparation cost, and good opaque temperature uniformity, and can meet the use requirements of wafer rapid thermal processing process.
[0030] The thickness of the annular SiC ceramic core layer is 0.1 to 0.3 mm. The thickness of the ultra-thin SiC ceramic core layer is less than the thickness of the final component, which is 0.4 mm. It provides a template for the deposition of the surface CVD SiC coating, and the template can be used as a part of the SiCEdge-Ring component, which reduces the deposition time of the CVD SiC coating and helps to significantly reduce the manufacturing cost.
[0031] The annular SiC ceramic core layer is prepared according to the following steps: Prepare SiC ceramic slurry with a volume fraction of ≥70 vol%; The SiC ceramic slurry is molded into a ring-shaped SiC ceramic body by a slip injection molding method; The SiC ceramic body is sequentially debinded and sintered to obtain a ring-shaped SiC ceramic core layer; The temperature during debinding is 600-1000°C and the debinding time is 1-3 hours. The sintering temperature is 1700-2100°C and the sintering time is 0.5-3h.
[0032] Exemplarily, the preparation process of the ultra-thin SiC ceramic core layer specifically includes: preparing a high volume fraction (> 70 vol%) SiC ceramic slurry, forming a SiC ceramic body by a slip injection molding method, performing low-temperature debinding and high-temperature sintering on the SiC ceramic body, and precision machining the sintered SiC ceramic to obtain an ultra-thin SiC ceramic core layer.
[0033] The SiC ceramic body obtained by slip casting with high volume fraction (> 70 vol%) SiC ceramic slurry is conducive to reducing volume shrinkage, preventing cracking, and improving the dimensional stability of the ceramic body during low-temperature debinding and high-temperature sintering. The SiC ceramic sintered at high temperature is porous with uniform pore distribution, and ultra-thin SiC ceramic core layer can be obtained by precision machining.
[0034] In the present invention, when the SiC ceramic core layer is densified, one or a combination of chemical vapor infiltration, polymer impregnation and cracking, and reaction melt infiltration is used to perform one or more densification treatments on the SiC ceramic core layer.
[0035] Using one or a combination of chemical vapor infiltration technology, polymer impregnation cracking technology, and reactive melt infiltration technology to perform one or more densification treatments on the ultra-thin SiC ceramic core layer helps to reduce the porosity of the ultra-thin SiC ceramic core layer, greatly increase the reflection path of the incident light in the ultra-thin SiC ceramic core layer, form efficient absorption of the incident light, significantly reduce light transmittance, and improve the temperature uniformity of the components under operating conditions.
[0036] Among them, the volume density of the SiC ceramic core layer after densification treatment is 2.5~3.2 g / cm 3 The densification treatment is beneficial to improve the density of the ultra-thin SiC ceramic core layer, significantly increase the strength and thermal conductivity of the core layer, and enhance the comprehensive strength and thermal conductivity of the SiC Edge-Ring component. The present invention preferably adopts multiple combinations to perform multiple densification treatments to ensure that the ultra-thin SiC ceramic core layer is sufficiently dense.
[0037] The thickness of the SiC coating is 0.05-0.20 mm; the SiC coating is dense and has no pore defects, and the grain size in the SiC coating is 0.5-20 μm.
[0038] The chemical vapor deposition method is used to deposit a SiC coating with a precisely controllable thickness on the surface of the ultra-thin SiC ceramic core layer. The preferred thickness range of the SiC coating is controlled at 0.05~0.20 mm. The SiC coating and the SiC ceramic core layer prepared by the chemical deposition method are both SiC in terms of material, and the difference in thermal expansion coefficient is very small and negligible, which avoids the problem of cracking and shedding of the surface coating caused by thermal mismatch between the core layer and the surface coating. The precise and controllable coating deposition thickness helps to deposit to the tolerance size range required by the SiCEdge-Ring component in one go, greatly reducing the finishing time and cost, and significantly increasing the production efficiency and processing yield of the SiCEdge-Ring component.
[0039] The chemical vapor deposition method is used to deposit a SiC coating with precisely controllable thickness on the surface of the ultra-thin SiC ceramic core layer. The SiC coating is dense and has no pore defects, and the grain size is 0.5~20 μm. By precisely controlling the chemical vapor deposition parameters, the surface CVD SiC coating of the SiCEdge-Ring component is dense and has no pore defects, which is beneficial to improving the overall integrity of the component, the stability of mechanical properties, and avoiding the overflow of particles and impurities. The SiC grain size in the coating is controlled to be 0.5~20 μm. Larger SiC grains help to improve the thermal conductivity of the coating and reduce the thermal stress generated inside the component during service.
[0040] The raw materials used to prepare SiC ceramic slurry include SiC micropowders of different particle sizes, dispersants and binders, wherein the different particle sizes of SiC micropowders are: 0.5μm, 2μm, 5μm, 10μm, 20μm; the dispersants are tetramethylammonium hydroxide and polyacrylamide, and the binders are carboxymethyl cellulose and polyvinyl alcohol.
[0041] The method for preparing SiC ceramic slurry comprises: First, weigh 1 part by mass of dispersant and add it to 8-13 parts by mass of deionized water and stir it thoroughly to dissolve. Then, add 97 parts by mass of graded SiC micropowder and mix it in a horizontal ball mill for 2 hours. The grinding medium used for ball milling is SiC grinding balls, and the ratio of grinding medium to graded SiC powder is 1.5-3:1. Then add another 1 part by mass of dispersant and continue ball milling for 2 hours. Finally, add 1 part by mass of binder and ball mill for 3 hours. The SiC ceramic slurry is obtained.
[0042] Among them, the mass ratio of different particle sizes from small to large in the graded SiC micropowder is 7:16:21:24:32; the mass ratio of dispersant, binder and SiC micropowder is 2:1:97 respectively; the mass ratio of tetramethylammonium hydroxide and polyacrylamide is 1:1; the mass ratio of carboxymethyl cellulose and polyvinyl alcohol is 1:1.
[0043] In the present invention, SiC coatings are deposited on the upper surface and the lower surface of the SiC ceramic core layer after densification treatment, respectively, including: The densified SiC ceramic core layer was placed in a chemical vapor deposition furnace, with MTS, H2 and Ar as the reaction gas, carrier gas and diluent gas respectively, and deposited at 1250-1400°C for 10-30h. Among them, the volume ratio of MTS, H2 and Ar is 1: (5-10): (1-3); The MTS flow rate is 0.5-1.5 L / min, the H2 flow rate is 2.5-7.5 L / min and the Ar flow rate is 1.0-4.5 L / min.
[0044] After depositing SiC coatings on the upper and lower surfaces of the densified SiC ceramic core layer, the method further includes: fine machining the SiC ceramic core layer with the SiC coatings by using a precision rotary table grinder, with a feed rate of 0.5-6 μm / min and a surface roughness Ra of less than 0.2 μm after machining.
[0045] The surface finishing of the SiC Edge-Ring component with a sandwich structure using a precision rotary table grinder can ensure the flatness and roughness requirements of the component. Controlling the feed rate at 0.5-6 μm / min is beneficial to reducing the occurrence of fragmentation during the finishing process of the component and improving the finishing yield of the component.
[0046] A second aspect of the present invention provides a SiC edge ring having a sandwich structure, that is, composed of an ultra-thin SiC ceramic at the core and a CVD SiC coating at the surface.
[0047] A third aspect of the present invention provides an application of a SiC edge ring in wafer annealing.
[0048] It should be noted that the experimental methods used in the present invention are all conventional methods unless otherwise specified; the reagents and materials used are all commercially available unless otherwise specified.
[0049] Example 1 A SiC Edge-Ring component for a rapid annealing furnace is prepared by the following method: (1) First, 70 vol% SiC ceramic slurry was prepared, and then the SiC ceramic ring blank was formed by the slip injection molding method. After the blank was completely dried at 105℃ for 72 h, the SiC ceramic blank was subjected to low-temperature debinding at 900℃ for 2 h and high-temperature sintering at 1900℃ for 2 h under vacuum. Finally, the sintered SiC ceramic was precision-machined using a high-precision CNC machining center to obtain an ultra-thin SiC ceramic core layer with a thickness of 0.25 mm.
[0050] (2) A 30 wt% phenolic resin ethanol solution was used as the carbon source. The polymer impregnation pyrolysis technology was used. The pyrolysis conditions were 1000℃ for 2 h. The impregnation pyrolysis was repeated three times to introduce an appropriate amount of resin carbon into the ultra-thin SiC ceramic core layer. Then, silicon powder was used as the silicon source. The reactive melt infiltration technology was used at 1700℃ for 3 h to allow the molten silicon to fully react with the resin carbon in the ultra-thin SiC ceramic core layer to obtain a reaction-dense ultra-thin SiC ceramic core layer.
[0051] (3) After the surface of the reaction-dense ultra-thin SiC ceramic core layer was lightly polished to a smooth state, it was placed on a deposition bracket and put into a chemical vapor deposition furnace. MTS, H2 and Ar were used as reaction gas and carrier gas dilution gas, respectively, with a volume ratio of 1:10:1 and flow rates of 0.5 L / min, 2.5 L / min and 1.0 L / min, respectively. Deposition was carried out at 1350°C for 10 h to obtain a CVD SiC coating with a single-side thickness of 85 μm and a SiC Edge-Ring component with a total thickness of 0.42 mm.
[0052] (4) After the sandwich-structured SiC Edge-Ring component is fixed on a special fixture, it is placed on a precision rotary table grinder to perform micro-finishing on the surface of the component at a feed rate of 0.5 μm / min. Finally, a SiC Edge-Ring component product with a thickness of 0.4 mm is obtained.
[0053] Example 2 A SiC Edge-Ring component for a rapid annealing furnace is prepared by the following method: (1) First, 75 vol% SiC ceramic slurry was prepared, and then the SiC ceramic ring blank was formed by the slip injection molding method. After the blank was completely dried at 105℃ for 72 h, the SiC ceramic blank was subjected to low-temperature debinding at 900℃ for 2 h and high-temperature sintering at 1900℃ for 2 h under vacuum. Finally, the sintered SiC ceramic was precision-machined using a high-precision CNC machining center to obtain an ultra-thin SiC ceramic core layer with a thickness of 0.20 mm.
[0054] (2) A 25 wt% polycarbosilane (PCS) toluene solution was used as the precursor solution. The polymer impregnation pyrolysis technology was used. The pyrolysis conditions were 1200℃ for 3 h. The impregnation pyrolysis was repeated 5 times to introduce a sufficient amount of polycarbosilane into the ultra-thin SiC ceramic core layer to convert it into silicon carbide ceramic. Then, silicon powder was used as the silicon source and the melt infiltration technology was used to keep the temperature at 1700℃ for 3 h so that the molten silicon could completely fill the residual pores in the ultra-thin SiC ceramic core layer, thereby obtaining a dense ultra-thin SiC ceramic core layer filled with molten silicon.
[0055] (3) After the surface of the melt-filled dense ultra-thin SiC ceramic core layer was lightly polished to a smooth state, it was placed on a deposition bracket and put into a chemical vapor deposition furnace. MTS, H2 and Ar were used as reaction gas and carrier gas dilution gas, respectively, with a volume ratio of 1:8:1.5 and a flow rate of 1.0 L / min, 4.0 L / min and 2.0 L / min, respectively. Deposition was carried out at 1250°C for 30 h to obtain a CVD SiC coating with a single-side thickness of 120 μm and a SiC Edge-Ring component with a total thickness of 0.44 mm.
[0056] (4) After the sandwich-structured SiC Edge-Ring component is fixed on a special fixture, it is placed on a precision rotary table grinder to perform micro-finishing on the surface of the component at a feed rate of 2 μm / min. Finally, a SiC Edge-Ring component product with a thickness of 0.4 mm is obtained. Figure 1 Shown is the product photo of the prepared SiC Edge-Ring component.
[0057] Example 3 A SiC Edge-Ring component for a rapid annealing furnace is prepared by the following method: (1) First, 72 vol% SiC ceramic slurry was prepared, and then the SiC ceramic ring blank was formed by the slip injection molding method. After the blank was completely dried at 105℃ for 72 h, the SiC ceramic blank was subjected to low-temperature debinding at 900℃ for 2 h and high-temperature sintering at 1900℃ for 2 h under vacuum. Finally, the sintered SiC ceramic was precision-machined using a high-precision CNC machining center to obtain an ultra-thin SiC ceramic core layer with a thickness of 0.30 mm.
[0058] (2) A 25 wt% polycarbosilane (PCS) toluene solution was used as the precursor solution. The polymer impregnation pyrolysis technique was used. The pyrolysis conditions were 1200℃ for 3 h. The impregnation pyrolysis was repeated three times to introduce an appropriate amount of polycarbosilane into the ultra-thin SiC ceramic core layer to convert it into silicon carbide ceramic. Then, a 30 wt% phenolic resin ethanol solution was used as the carbon source. The polymer impregnation pyrolysis technique was used. The pyrolysis conditions were 1000℃ for 2 h. The impregnation pyrolysis was repeated twice to introduce an appropriate amount of resin carbon into the ultra-thin SiC ceramic core layer. Finally, silicon powder was used as the silicon source. The reactive melt infiltration technique was used at 1700℃ for 3 h to allow the molten silicon to fully react with the resin carbon in the ultra-thin SiC ceramic core layer to obtain a dense ultra-thin SiC ceramic core layer.
[0059] (3) After the surface of the reaction-dense ultra-thin SiC ceramic core layer was lightly polished to a smooth state, it was placed on a deposition bracket and put into a chemical vapor deposition furnace. MTS, H2 and Ar were used as reaction gas and carrier gas dilution gas, respectively, with a volume ratio of 1:7:3 and flow rates of 1.0 L / min, 5.0 L / min and 3.0 L / min, respectively. Deposition was carried out at 1300°C for 10 h to obtain a CVD SiC coating with a single-side thickness of 70 μm and a SiC Edge-Ring component with a total thickness of 0.44 mm.
[0060] (4) After the sandwich-structured SiC Edge-Ring component is fixed on a special fixture, it is placed on a precision rotary table grinder to perform micro-finishing on the surface of the component at a feed rate of 3 μm / min. Finally, a SiC Edge-Ring component product with a thickness of 0.4 mm is obtained.
[0061] Example 4 A SiC Edge-Ring component for a rapid annealing furnace is prepared by the following method: (1) First, 78 vol% SiC ceramic slurry was prepared, and then the SiC ceramic ring blank was formed by the slip injection molding method. After the blank was completely dried at 105℃ for 72 h, the SiC ceramic blank was subjected to low-temperature debinding at 900℃ for 2 h and high-temperature sintering at 1900℃ for 2 h under vacuum. Finally, the sintered SiC ceramic was precision-machined using a high-precision CNC machining center to obtain an ultra-thin SiC ceramic core layer with a thickness of 0.12 mm.
[0062] (2) The ultra-thin SiC ceramic core layer was placed on a deposition bracket and placed in a chemical vapor deposition furnace. MTS, H2 and Ar were used as the reaction gas and carrier gas diluent gas, respectively, with a volume ratio of 1:10:3 and a flow rate of 0.5 L / min, 3.0 L / min and 1.0 L / min, respectively, and the deposition was carried out at 1100°C for 30 h. Then, a 20 wt% polycarbosilane (PCS) toluene solution was used as the precursor solution, and the polymer impregnation pyrolysis technology was used. The pyrolysis condition was 1200°C for 3 h, and the impregnation pyrolysis was repeated twice to introduce sufficient polycarbosilane into the ultra-thin SiC ceramic core layer to convert silicon carbide ceramics, so as to completely fill the residual pores in the ultra-thin SiC ceramic core layer and obtain a dense ultra-thin SiC ceramic core layer.
[0063] (3) After the surface of the dense ultra-thin SiC ceramic core layer was lightly polished to a smooth state, it was placed on a deposition bracket and put into a chemical vapor deposition furnace. MTS, H2 and Ar were used as the reaction gas and carrier gas dilution gas, respectively, with a volume ratio of 1:5:2 and a flow rate of 1.5 L / min, 7.5 L / min and 3.0 L / min, respectively. Deposition was carried out at 1400°C for 15 h to obtain a CVD SiC coating with a single-side thickness of 200 μm and a SiC Edge-Ring component with a total thickness of 0.52 mm.
[0064] (4) After the sandwich-structured SiC Edge-Ring component is fixed on a special fixture, it is placed on a precision rotary table grinder to perform micro-finishing on the surface of the component at a feed rate of 6 μm / min. Finally, a SiC Edge-Ring component product with a thickness of 0.4 mm is obtained. Figure 3Shown is the product photo of the prepared SiC Edge-Ring component.
[0065] Example 5 A SiC Edge-Ring component for a rapid annealing furnace is prepared by the following method: (1) First, 72 vol% SiC ceramic slurry was prepared, and then the SiC ceramic ring blank was formed by the slip injection molding method. After the blank was completely dried at 105℃ for 72 h, the SiC ceramic blank was subjected to low-temperature debinding at 900℃ for 2 h and high-temperature sintering at 1900℃ for 2 h under vacuum. Finally, the sintered SiC ceramic was precision-machined using a high-precision CNC machining center to obtain an ultra-thin SiC ceramic core layer with a thickness of 0.22 mm.
[0066] (2) The ultra-thin SiC ceramic core layer was placed on a deposition bracket and placed in a chemical vapor deposition furnace. MTS, H2 and Ar were used as the reaction gas and carrier gas diluent gas, respectively, with a volume ratio of 1:8:3 and a flow rate of 1.0 L / min, 3.5 L / min and 1.0 L / min, respectively, and the deposition was carried out at 1150℃ for 20 h. Then, a phenolic resin ethanol solution with a mass concentration of 25 wt% was used as the carbon source, and a polymer impregnation pyrolysis technique was used. The pyrolysis condition was 1000℃ for 2 h, and the impregnation pyrolysis was repeated 3 times to introduce an appropriate amount of resin carbon into the ultra-thin SiC ceramic core layer. Then, silicon powder was used as the silicon source and a reactive melt infiltration technique was used at 1700℃ to fully react the molten silicon with the resin carbon in the ultra-thin SiC ceramic core layer for 3 h to obtain a dense ultra-thin SiC ceramic core layer.
[0067] (3) After the surface of the dense ultra-thin SiC ceramic core layer was lightly polished to a smooth state, it was placed on a deposition bracket and put into a chemical vapor deposition furnace. MTS, H2 and Ar were used as the reaction gas and carrier gas dilution gas, respectively, with a volume ratio of 1:5:2 and a flow rate of 1.0 L / min, 5.0 L / min and 1.0 L / min, respectively. Deposition was carried out at 1300°C for 10 h to obtain a CVD SiC coating with a single-side thickness of 115 μm and a SiC Edge-Ring component with a total thickness of 0.45 mm.
[0068] (4) After the sandwich-structured SiC Edge-Ring component is fixed on a special fixture, it is placed on a precision rotary table grinder to perform micro-finishing on the surface of the component at a feed rate of 3 μm / min. Finally, a SiC Edge-Ring component product with a thickness of 0.4 mm is obtained.
[0069] Example 6 A SiC Edge-Ring component for a rapid annealing furnace is prepared by the following method: (1) First, 70 vol% SiC ceramic slurry was prepared, and then the SiC ceramic ring blank was formed by the slip injection molding method. After the blank was completely dried at 105℃ for 72 h, the SiC ceramic blank was subjected to low-temperature debinding at 900℃ for 2 h and high-temperature sintering at 1900℃ for 2 h under vacuum. Finally, the sintered SiC ceramic was precision-machined using a high-precision CNC machining center to obtain an ultra-thin SiC ceramic core layer with a thickness of 0.27 mm.
[0070] (2) The ultra-thin SiC ceramic core layer was placed on a deposition bracket and put into a chemical vapor deposition furnace. MTS, H2 and Ar were used as the reaction gas and carrier gas dilution gas, respectively, with a volume ratio of 1:8:3 and flow rates of 1.0 L / min, 3.5 L / min and 1.0 L / min, respectively. Deposition was carried out at 1150°C for 25 h.
[0071] A 20 wt% polycarbosilane (PCS) toluene solution was used as the precursor solution. The polymer impregnation pyrolysis technology was used. The pyrolysis conditions were 1200℃ for 3 h. The impregnation pyrolysis was performed once to introduce an appropriate amount of polycarbosilane into the ultra-thin SiC ceramic core layer to convert it into silicon carbide ceramics. Then, a 15 wt% phenolic resin ethanol solution was used as the carbon source. The polymer impregnation pyrolysis technology was used. The pyrolysis conditions were 1000℃ for 2 h. The impregnation pyrolysis was performed once to introduce an appropriate amount of resin carbon into the ultra-thin SiC ceramic core layer. Finally, silicon powder was used as the silicon source. The reactive melt infiltration technology was used at 1700℃ to make the molten silicon and the resin carbon in the ultra-thin SiC ceramic core layer fully react for 2 h to obtain a reaction-dense ultra-thin SiC ceramic core layer.
[0072] (3) After the surface of the dense ultra-thin SiC ceramic core layer was lightly polished to a smooth state, it was placed on a deposition bracket and put into a chemical vapor deposition furnace. MTS, H2 and Ar were used as the reaction gas and carrier gas dilution gas, respectively, with a volume ratio of 1:5:1.5 and a flow rate of 1.5 L / min, 5.0 L / min and 1.5 L / min, respectively. Deposition was carried out at 1350°C for 12 h to obtain a CVD SiC coating with a single-side thickness of 100 μm and a SiC Edge-Ring component with a total thickness of 0.47 mm.
[0073] (4) After the sandwich-structured SiC Edge-Ring component is fixed on a special fixture, it is placed on a precision rotary table grinder to perform micro-finishing on the surface of the component at a feed rate of 4 μm / min. Finally, a SiC Edge-Ring component product with a thickness of 0.4 mm is obtained.
[0074] Comparative Example 1 A SiC Edge-Ring component for a rapid annealing furnace is prepared by the following reaction sintering method: Firstly, SiC ceramic slurry with a carbon powder content of 10 wt% was prepared, and then the SiC ceramic ring blank (thickness ≥ 3 mm) was formed by the slip injection molding method. After the blank was completely dried at 105°C for 72 h, the SiC ceramic blank was buried in silicon powder with a weight three times that of the blank and sintered at 1700°C for 2 h under vacuum. Finally, a high-precision CNC machining center was used to precisely process the dense SiC ceramics sintered by reaction, and a SiC Edge-Ring component product with a thickness of 0.40 mm was obtained.
[0075] Comparative Example 2 A SiC Edge-Ring component for a rapid annealing furnace is prepared by the following chemical vapor deposition method: First, the isostatic graphite block was processed into a graphite ring blank with a thickness of 5 mm using a high-precision CNC machining center. Then it was placed on a deposition bracket and put into a chemical vapor deposition furnace. MTS, H2 and Ar were used as the reaction gas and carrier gas dilution gas, respectively. The deposition was carried out at 1350℃ for 150 h to obtain a graphite silicon carbide ring with a CVD SiC coating thickness of more than 3 mm. The graphite silicon carbide ring was cut along the thickness center line using a diamond sand wire cutting machine, and the graphite substrate was removed by keeping it at 600℃ in a muffle furnace for 72 h. Finally, the CVD SiC coating was precisely processed using a high-precision CNC machining center to obtain a SiC Edge-Ring component product with a thickness of 0.40 mm.
[0076] Comparative Example 3 A SiC Edge-Ring component for a rapid annealing furnace, which is prepared by a hot pressing sintering method: First, a SiC ceramic slurry with a carbon powder content of 1 wt% was prepared, and then a spherical ceramic powder with a particle size of 0.15 mm was prepared by a spray granulation method. After the ceramic powder was loaded into a special sintering tool, a hot-pressed SiC ceramic ring with a thickness of > 3 mm was sintered at 2000℃ for 3 h under a mechanical pressure of 40 MPa in a hot-pressed sintering furnace. Finally, a high-precision CNC machining center was used to precisely machine the hot-pressed SiC ceramic ring to obtain a SiC Edge-Ring component product with a thickness of 0.40 mm.
[0077] The SiC Edge-Ring component products in the above embodiments and comparative examples were subjected to relevant performance tests, and the test methods are described as follows: (1) Surface purity The impurity element content on the surface of the SiC Edge-Ring component product was measured using a glow discharge mass spectrometer (GDMS), and the test results are recorded in Table 1; the GDMS results of the component provided in Example 3 are shown in Table 2.
[0078] Thermal conductivity The thermal conductivity of the SiC Edge-Ring component product was measured using a laser thermal conductivity meter, and the test results are recorded in Table 1.
[0079] The light transmittance of the SiC Edge-Ring component product was measured using a UV-Vis-IR spectrophotometer, and the test results are recorded in Table 1.
[0080] (4) Bending strength The bending strength of the SiC Edge-Ring component product was measured using a universal testing machine, and the test results are recorded in Table 1.
[0081] From the results in Table 1 and Table 2, it can be seen that the SiC Edge-Ring component with sandwich structure characteristics prepared in the embodiment of the present invention not only has high surface purity, excellent thermal conductivity, complete opacity and good mechanical properties, but also has an extremely short processing cycle, which means that the SiC Edge-Ring component for a rapid annealing furnace provided by the present invention has low processing cost and high processing yield (> 75%). Compared with the comparative example, the technical advantages of the present invention are more significant.
[0082] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
[0083] Table 1 Test results of components provided by the embodiments and comparative examples
[0084] From the test data of the reaction sintered component provided in Comparative Example 1 in Table 1, it can be seen that its impurity content is greater than 100ppm, which cannot meet the requirements of the technical indicators of the impurity content of the component in the semiconductor field (<1ppm). In contrast, the component provided by the present invention has a special sandwich structure feature, that is, the upper and lower surfaces of the component are both high-purity CVD SiC, and the impurity content is less than 1ppm, which can meet the requirements of the technical indicators of the impurity content of the component in the semiconductor field. Comparative Example 2 is a solid CVD SiC component prepared by a graphite template combined with a CVD process. Although the impurity content technical indicators fully meet the requirements, due to the single-direction growth mechanism of SiC grains during the deposition process of the solid CVD SiC, the SiC grains grow in a larger size in the thickness direction of the component, the number of grain boundaries is relatively small, and it has transmittance to ultraviolet-visible-infrared light in the wavelength range of 200 to 1500nm (transmittance>20%), which cannot meet the requirements of the transmittance of light in this wavelength range for components used in rapid annealing furnaces (transmittance<0.5%). Since the heating system of the rapid annealing furnace is an array infrared halogen lamp heating system, components with good light transmittance will cause local uneven heating during use, resulting in actual problems such as stress concentration and damage to the components. Therefore, the components must be light-impermeable (transmittance < 0.5%). Obviously, the components provided in Comparative Example 2 cannot meet the use requirements. The components provided by the present invention have special sandwich structure characteristics, with a powder sintered SiC ceramic core layer in the middle. After grading optimization design, the particle stacking volume fraction of the SiC ceramic core layer is > 70 vol%. The high SiC particle stacking fraction produces a large number of disordered grain boundaries, which makes the SiC ceramic core layer of the component have an excellent scattering effect on ultraviolet-visible-infrared light in the wavelength range of (200-1500nm). Therefore, the components provided by the present invention have very good light opacity (transmittance < 0.1%) in the ultraviolet-visible-infrared light in the wavelength range of (200-1500nm), which can meet the technical index requirements of light opacity of components in the semiconductor field.
[0085] Comparative Example 3 is a component prepared by hot pressing sintering process. This component is a special accessory for rapid annealing furnace provided by a foreign supplier and is only used as a comparison in the present invention. In addition, a common point of the SiC components provided by Comparative Examples 1, 2 and 3 is that a dense ceramic blank with a thickness of >3mm is first prepared, and then a high-precision CNC machining center is used to process the dense ceramic blank with an initial thickness of >3mm to a finished product feature of 0.4mm, and the processing removal is very large. However, the dense SiC ceramic is very brittle, which makes the processing efficiency of the component very low. The processing cycle of a product reaches 25 to 28 days, and the risk of processing fragmentation is very high (yield <50%). The component preparation method provided by the present invention has significantly smaller processing difficulty and processing cycle, which benefits from the technical advantages of the net size preparation of the present invention. The first is the preparation of an ultra-thin SiC ceramic core layer. The SiC ceramic prepared in this step is porous and after toughening treatment, the risk of processing fragmentation is much lower than that of dense SiC ceramics. Then, a variety of combined densification processes were used to densify the ultra-thin SiC ceramic core layer, significantly increasing the volume density and strength of the ultra-thin SiC ceramic core layer. Finally, precise CVD process control was used to deposit a SiC coating of a specified thickness on the upper and lower surfaces of the ultra-thin SiC ceramic core layer, leaving only a few tens of microns of processing volume, greatly shortening the amount of finishing, significantly reducing the finishing cycle (shortened to 5 days) and the risk of fragmentation, and greatly improving the efficiency and yield of component preparation.
[0086] Table 2 shows the GDMS results of the components provided in Example 3
[0087] Table 2 shows the GDMS results of the components provided in Example 3. It can be seen from Table 2 that the surface impurity content of the SiC components provided by the present invention is very low, <1ppm, which fully meets the requirements of the semiconductor field for the technical indicators of impurity content of components (<1ppm).
[0088] Figure 2 This is a cross-sectional SEM image of the SiC Edge-Ring component product prepared in Example 2. Figure 2 The cross-sectional SEM image of the component shows that the SiC Edge-Ring component prepared in Example 2 of the present invention exhibits a sandwich structure, consisting of an ultra-thin SiC ceramic core layer in the middle and CVD SiC coatings on the upper and lower surfaces. The ultra-thin SiC ceramic core layer is about 0.2 mm thick and is dense, and is well bonded to the CVD SiC coating on the surface.
[0089] Figure 4 This is a cross-sectional SEM image of the SiC Edge-Ring component product prepared in Example 4. Figure 4From the cross-sectional SEM image of the component, it can be seen that the SiC Edge-Ring component prepared in Example 4 of the present invention exhibits a sandwich structure, consisting of an ultra-thin SiC ceramic core layer in the middle and CVD SiC coatings on the upper and lower surfaces. The ultra-thin SiC ceramic core layer is about 0.1 mm thick and has good compactness. The CVD SiC coating on the surface is about 0.15 mm thick and is dense. The ultra-thin SiC ceramic core layer and the SiC coating are well combined.
[0090] Figure 5 The surface XRD diagram of the SiC Edge-Ring component product prepared in Example 1. Figure 5 From the XRD results, it can be seen that the surface of the component is a CVD SiC coating that is directionally deposited and grown along the thickness direction.
[0091] Figure 6 This is the light transmittance test result of the SiC Edge-Ring component product prepared in Example 6. Figure 6 From the light transmittance test results and the data in Table 1, it can be seen that the component provided by the present invention has very good light opacity (transmittance <0.1%) in the ultraviolet-visible-infrared light within the wavelength range of (200-1500nm), which can meet the light opacity technical indicator requirements of the components in the semiconductor field.
[0092] Figure 7 This is the bending strength test result of the SiC Edge-Ring component product prepared in Example 4. Figure 7 The bending strength test results obtained by performing a three-point bending test on the in-situ sample of the component provided in Example 4. Figure 7 The four curves represent samples 1# to 4#, all of which are from the components provided in Example 4. It can be seen from the stress-strain curve that before reaching the maximum stress, the stress-strain curve changes linearly and the slope remains constant, indicating that the sample exhibits elastic deformation behavior during the bending loading process. Until the bending stress reaches the ultimate bending strength of the sample, the stress-strain curve of the sample suddenly drops, indicating that the sample breaks instantly at this time. From the ultimate stress values of the four curves corresponding to the four samples, it can be seen that the bending strength of the component provided in Example 4 is between 400 and 450 MPa, with an average value of 425 MPa. Compared with the bending strength data of the embodiments and comparative examples listed in Table 1, it can be seen that the components prepared by the present invention have excellent mechanical properties, especially Example 4, which is the best embodiment, has the highest bending strength, which fully meets the mechanical performance index requirements of the rapid annealing furnace for the component (bending strength greater than 200 MPa).
[0093] In summary, the present invention provides a SiC edge ring and a preparation method thereof, and the component has a sandwich structure feature, that is, it is composed of an ultra-thin SiC ceramic located in the core and a CVD SiC coating on the surface. The preparation process of the SiCEdge-Ring component with this sandwich structure includes: preparation of an ultra-thin SiC ceramic core layer, densification of the ultra-thin SiC ceramic core layer, precise deposition of the surface CVD SiC coating, and surface finishing of the SiC Edge-Ring component with a sandwich structure. The SiC Edge-Ring component and the preparation method thereof provided by the present invention have the advantages of low requirements for sintering equipment, small net size processing amount, high surface purity, excellent thermal conductivity, short preparation cycle and low cost, and can meet the use requirements of wafer rapid thermal processing process.
[0094] The present invention describes preferred embodiments and their effects. However, those skilled in the art may make additional changes and modifications to these embodiments once they are aware of the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0095] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing a SiC edge ring, characterized in that: The following steps are involved: Preparing a ring-shaped SiC ceramic core layer; Densification treatment of SiC ceramic core layer; SiC coatings are deposited on the upper surface and the lower surface of the SiC ceramic core layer after densification treatment to obtain SiC edge rings.
2. The method for preparing a SiC edge ring according to claim 1, characterized in that: The thickness of the annular SiC ceramic core layer is 0.1-0.3 mm.
3. The method for preparing a SiC edge ring according to claim 1, characterized in that: The annular SiC ceramic core layer is prepared according to the following steps: Prepare SiC ceramic slurry with a volume fraction of ≥70 vol%; The SiC ceramic slurry is molded into a ring-shaped SiC ceramic body by a slip injection molding method; The SiC ceramic body is sequentially debinded and sintered to obtain a ring-shaped SiC ceramic core layer; The temperature during debinding is 600-1000℃ and the debinding time is 1-3h. The sintering temperature is 1700-2100°C and the sintering time is 0.5-3h.
4. The method for preparing a SiC edge ring according to claim 1, characterized in that: When the SiC ceramic core layer is subjected to densification treatment, one or a combination of chemical vapor infiltration method, polymer impregnation cracking method, and reaction melt infiltration method is used to perform densification treatment on the SiC ceramic core layer once or multiple times.
5. The method for preparing a SiC edge ring according to claim 1, characterized in that: The volume density of the SiC ceramic core layer after densification treatment is 2.5~3.2 g / cm 3 .
6. The method for preparing a SiC edge ring according to claim 1, characterized in that: The thickness of the SiC coating is 0.05-0.20 mm; the SiC coating is dense and has no pore defects, and the grain size in the SiC coating is 0.5-20 μm.
7. The method for preparing a SiC edge ring according to claim 1, characterized in that: The SiC coating is deposited on the upper surface and the lower surface of the SiC ceramic core layer after the densification treatment, including: The densified SiC ceramic core layer was placed in a chemical vapor deposition furnace, with MTS, H2 and Ar as the reaction gas, carrier gas and diluent gas respectively, and deposited at 1250-1400°C for 10-30h; Among them, the volume ratio of MTS, H2 and Ar is 1: (5-10): (1-3); The MTS flow rate is 0.5~1.5L / min; the H2 flow rate is 2.5~7.5L / min; and the Ar flow rate is 1.0~4.5L / min.
8. The method for preparing a SiC edge ring according to claim 1, characterized in that: After depositing SiC coatings on the upper and lower surfaces of the densified SiC ceramic core layer, the method further includes: fine machining the SiC ceramic core layer with the SiC coatings by using a precision rotary table grinder, with a feed rate of 0.5 to 6 μm / min and a surface roughness Ra of less than 0.2 μm after machining.
9. A SiC edge ring prepared by the method according to any one of claims 1 to 8.
10. Use of the SiC edge ring according to claim 9 in wafer annealing.
Citation Information
Patent Citations
Beta-SiC ceramic and preparation method thereof
CN118724594A
SiC / SiC composite material cladding tube as well as preparation method and application thereof
CN119161199A
Silicon carbide ceramic material with super-compact surface layer and preparation method thereof
CN119330719A
Sandwiched type structure SIC base composite material light reflection mirrow and its preparation method
CN1719287A